Determinación del estado socio ambiental, localidad de Pampa Hermosa, Yurimaguas - Gallardo Cárdenas, Verónica Del Pilar (2013)
The Pampa Hermosa town located within the jurisdiction of the Alto Amazonas Province department of Loreto, in these past few years has experienced a population growth and urban development to cause the development of the agro-industrial activity of the oil palm. Through this research work was able to determine the current situation at the level of social diagnosis and environmental conditions, in order to raise indicators for assessment of his development and achieve the desired sustainable development of the community as a whole. The field work consisted in the implementation of 165 survey to the community, direct interviews with local authorities, politicians, organizations of databases among others, as well as the compilation of statistical information of the state institutions on themes such as public safety, health, accident, education, among others; all this development in a total of 05 months. As result of the social diagnosis: 1 00 % of the population does not possess system of water supply and sewer, the predominant material (45 %) for construction of housings is the adobe or quincha; the educational offer goes from the initial leve! to the secondary level, the demand of the higher level is covered either in Yurimaguas or Tarapoto depending on the economy and the family specialties to choose from; health ca re is carried out in a 87.27 per cent in the Health Center, the 7.27 % with natural medicine; the economic activity that meets the needs of the population in a 70% is agricultura with crops of palm, palm, cocoa, maize, rice, among others, still very few opportunities for social service activities which is reflectad in the high insecurity the 56.36 % of the population qualifies to Pampa Hermosa as an unsafe place, this in tum can be seen with the complaints registered by the PNP (60% of complaints for offenses against the heritage). Of the environmental diagnosis of the locality of Pampa Hermosa, it is found that the principal environmental problematic is the pollution in 33 %, the perception of affectation of the environment across the productiva activities in 62 % recognizes that if he falls ill; existing a predisposition of 37 % of the population to the conservation of the remaining forests for conservation of the environment, 13 % as the air and 7 % in conservation of the animals; but that in tum meets threatened by increase of offers in productiva development of cultures as Palm, Palmetto and Cacao. Finally the prioritization of Socio-environmental indicators, to address factors of social and environmental of the urban area should address topics such as: growth of the urban population, basic services, environmental sanitation, public safety, environmental awareness. Key words: environmental awareness, environmental conditions.